The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/0103-6513.20200009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of selection and combination strategies for demand forecasting methods

Abstract: Paper aims: In this study, effective strategies to combine and select forecasting methods are proposed. In the selection strategy, the best performing forecasting method from a pool of methods is selected based on its accuracy, whereas the combination strategies are based on the mean methods' outputs and on the methods' accuracy. Originality: Despite the large amount of work in this area, the actual literature lacks of selection and combination strategies of forecasting methods for dealing with intermittent ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In order to achieve good forecasting accuracy, it is important to use an appropriate forecasting strategy. Research on forecasting strategies have been long in the focus of numerous researchers (Bates and Granger 1969;Makridakis 1988;Bunn 1989;De Menezes et al 2000;Armstrong 2001;Timmermann 2006;Hall and Mitchell 2007;Clark and McCracken 2009;Geweke and Amisano 2011;Kourentzes et al 2014;Fildes and Petropoulos 2015;Nowotarski et al 2016;Pinar et al 2017;Kourentzes et al 2019;Galvão Bandeira et al 2020;Giacalone 2021;Kang et al 2021). In a seminal study on strategies about improving the forecasts accuracy, Bates and Granger (1969) confirmed that combining the forecasts using different models, instead of relying on the individual models, can improve the accuracy of predictions.…”
Section: Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve good forecasting accuracy, it is important to use an appropriate forecasting strategy. Research on forecasting strategies have been long in the focus of numerous researchers (Bates and Granger 1969;Makridakis 1988;Bunn 1989;De Menezes et al 2000;Armstrong 2001;Timmermann 2006;Hall and Mitchell 2007;Clark and McCracken 2009;Geweke and Amisano 2011;Kourentzes et al 2014;Fildes and Petropoulos 2015;Nowotarski et al 2016;Pinar et al 2017;Kourentzes et al 2019;Galvão Bandeira et al 2020;Giacalone 2021;Kang et al 2021). In a seminal study on strategies about improving the forecasts accuracy, Bates and Granger (1969) confirmed that combining the forecasts using different models, instead of relying on the individual models, can improve the accuracy of predictions.…”
Section: Strategiesmentioning
confidence: 99%
“…For this purpose, different selection criteria were used. Galvão Galvão Bandeira et al (2020) stated that the selection can be based on the time series characteristics (Petropoulos et al 2018), the forecasting model performance (Wang and Petropoulos 2016;Fildes and Petropoulos 2015), the information criteria (Qi and Zhang 2001), or the judgmental expert selection (Petropoulos et al 2018). Kourentzes et al (2014) proposed a novel algorithm that aims to mitigate the importance of model selection, while increasing the accuracy.…”
Section: Strategiesmentioning
confidence: 99%
“…The work of (Bandeira et al, 2020) proposes a forecasting application strategy considering two procedures: the combination of state-of-the-art forecasting methods and the selection of forecasting methods based on the accuracy of the models. The authors propose two combination strategies: simple mean and weighted mean based on the accuracy of the methods.…”
Section: Related Workmentioning
confidence: 99%
“…Demand forecasting is one of the critical activities of supply chain management (Crum & Palmatier, 2003). As it refers to predicting future sales, demand forecasts support managerial decisions and operational planning throughout the supply chain (Bandeira et al, 2020). For instance, Sales and Operations Planning (S&OP) recognizes demand forecasts as an essential input for the process (Seeling et al, 2019).…”
Section: Introductionmentioning
confidence: 99%